Doing Critical and Creative Research in Adult Education Case Studies in Methodology and Theory - Grummell, Bernie; Finnegan, Fergal (Research on the Education and Learning of Adults, 2020)
Doing Critical and Creative Research in Adult Education brings together leading and emerging scholars in adult education in order to capture the vitality and complexity of contemporary adult education research, marked by the desire to conduct critical and creative research with rather than about people.; Readership: Adult education researchers and academics, adult education practitioners, postgraduate students and researchers in adult education and education, social science researchers and academics, arts and humanities researchers and academics.